2019
DOI: 10.1016/j.stem.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Wnt4 from the Niche Controls the Mechano-Properties and Quiescent State of Muscle Stem Cells

Abstract: Highlights d Wnt4 from the muscle fiber maintains SC quiescence d Wnt4 activates Rho in QSCs to maintain their tension, shape, and niche retention d Rho represses YAP to prevent SC activation d Loss of myofiber-derived Wnt4 accelerates muscle regeneration after injury

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
125
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 75 publications
9
125
1
Order By: Relevance
“…Our results are comparable to mouse, where the density of MuSCs ranges from 5 to 20 cells/mm 2 ( Fig. 1 ) ( Parisi et al, 2015 ; Eliazer et al, 2019 ; Schaaf et al, 2018 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Our results are comparable to mouse, where the density of MuSCs ranges from 5 to 20 cells/mm 2 ( Fig. 1 ) ( Parisi et al, 2015 ; Eliazer et al, 2019 ; Schaaf et al, 2018 ).…”
Section: Resultssupporting
confidence: 87%
“…Our in situ evaluations ( Fig. 1 ) showed an average of 10 Pax7 + cells per mm 2 , which is also comparable to the number of MuSCs per mm 2 in mouse ( Parisi et al, 2015 ; Eliazer et al, 2019 ; Schaaf et al, 2018 ). Given the above and the larger size of the rat muscles, one can isolate a greater number of MuSCs from the rat.…”
Section: Discussionsupporting
confidence: 78%
“…We verified the specificity of the coupled antibodies (listed in Table S3 ) by performing the corresponding isotypic controls ( Figure S2 A). In addition, we used fluorescence-activated cell sorting (FACS) to sort cells stained with these coupled antibodies and counterstained them with antibodies commonly used for immunofluorescence (IF) in the field ( Figures S2 B–S2D; Table S4 ) ( Eliazer et al., 2019 ; Machado et al., 2017 ; Paris et al., 2016 ). Finally, we confirmed that endogenous PAX7 expression analyzed with coupled anti-PAX7-AF647 antibody correlated with GFP expression in myogenic cells derived from Tg:PAX7-nGFP mouse muscles ( Figure S2 E).…”
Section: Resultsmentioning
confidence: 99%
“…The modified β-catenin is now free to translocate to the nucleus, where it exerts its transcriptional activity and induces the expression of multiple Wnt ligands that feed forward to promote and reinforce mesoderm specification and gastrulation (Bienz, 2005;Chhabra et al, 2019;Kemp et al, 2005;Lindsley et al, 2006;Martyn et al, 2019;Laralynne Przybyla et al, 2016). Notably, Wnt/β-catenin signaling is conserved among model organisms and plays multiple roles throughout the course of embryogenesis and in adult stem cells (Clevers, 2006;Eliazer et al, 2019;Petersen and Reddien, 2009;van Amerongen and Nusse, 2009), implying that the tension-regulated activation of the pathway that we illustrate here is likely also conserved and re-used throughout development. In fact, Farge and colleagues demonstrated that the same Src-mediated phosphorylation at Y654 and subsequent release of junctional β-catenin occurs during mesoderm invagination in Drosophila embryos (Röper et al, 2018).…”
Section: Discussionmentioning
confidence: 99%